2020
DOI: 10.1007/s11356-020-07666-y
|View full text |Cite
|
Sign up to set email alerts
|

Marine macroalgae as food for earthworms: growth and selection experiments across ecotypes

Abstract: Historically, subsistence farmers around the Atlantic coast of NW Europe utilized marine algae as a fertilizer in agroecosystems, a practice that continued in small areas and is now considered to have real potential for re-establishing sustainable food production systems on marginal soils. Earthworms form a significant component of soil fauna, and their ecosystem services are welldocumented. Therefore, palatability of marine organic amendments to faunal detritivores of terrestrial systems is of interest. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Meanwhile, the tendency of cocoons and immature occurred in the concentration of 60% (C60) (Table 1). These results re-emphasized that the application of K. alvarezii extract through the soil did not have a significant effect on reducing microbe populations [28], especially from the Phertima sp. 1±2a 1±2a 17±4a 20±4a Note: Numbers followed by the same letter in the same column showed no significant difference according to the LSD test at the p < 0.05 level.…”
Section: Earthworm Abundance and Total Of Amf Sporementioning
confidence: 60%
See 1 more Smart Citation
“…Meanwhile, the tendency of cocoons and immature occurred in the concentration of 60% (C60) (Table 1). These results re-emphasized that the application of K. alvarezii extract through the soil did not have a significant effect on reducing microbe populations [28], especially from the Phertima sp. 1±2a 1±2a 17±4a 20±4a Note: Numbers followed by the same letter in the same column showed no significant difference according to the LSD test at the p < 0.05 level.…”
Section: Earthworm Abundance and Total Of Amf Sporementioning
confidence: 60%
“…The survival of Pheretima sp was caused by the application of seaweed extracts to the soil, which further triggered their activities in modulating bacteria and fungi that were positively correlated with plant productivity [28]. Based on the soil fungi group, AMF played a functional role in facilitating plant access to nutrients and water, as well as stimulating root growth [29].…”
Section: Earthworm Abundance and Total Of Amf Sporementioning
confidence: 99%
“…In low input agricultural systems where fertilisation is organic, earthworms can notably increase plant yield through enhancement of nitrogen cycling and availability [40] and possibly by similar effects on soil phosphorus [41]. It has been recently shown that earthworms can feed on kelp [9], the main organic amendment used at our study sites, and potentially increase the mineralisation of plant nutrients from it. In the lazybeds, both abandoned and presently active, earthworms were present in sufficiently high numbers for effects on nutrient cycling and plant growth to be anticipated.…”
Section: Discussionmentioning
confidence: 75%
“…Combined with high annual rainfall up to, for instance, 1,800 mm on the Isle of Rum [7], these soils require management to make them viable for crop production. Many coastal soils were amended with brown seaweeds (kelp and fucoids) [8] produced in abundance in the littoral zone and collected from the shore, often after storm dislodgement [9]. In some areas this marine bounty was simply applied directly to the land or may have been composted first, perhaps with the addition of animal dung [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation